Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To solve the problem, we need to find which expression is equivalent to [tex]\(9^2 + 4^2\)[/tex].
Let's start by evaluating [tex]\(9^2 + 4^2\)[/tex].
[tex]\[ 9^2 \][/tex] means 9 multiplied by itself, which is:
[tex]\[ 9 \times 9 = 81 \][/tex]
[tex]\[ 4^2 \][/tex] means 4 multiplied by itself, which is:
[tex]\[ 4 \times 4 = 16 \][/tex]
Adding them together:
[tex]\[ 81 + 16 = 97 \][/tex]
Now we will check each provided option to find which one equals 97.
1. [tex]\((9 + 4)^2\)[/tex]
[tex]\[ 9 + 4 = 13 \][/tex]
[tex]\[ 13^2 = 13 \times 13 = 169 \][/tex]
This is not equivalent to 97.
2. [tex]\((9 \times 4)^2\)[/tex]
[tex]\[ 9 \times 4 = 36 \][/tex]
[tex]\[ 36^2 = 36 \times 36 = 1296 \][/tex]
This is not equivalent to 97.
3. [tex]\((9 \times 9) + (4 \times 4)\)[/tex]
[tex]\[ 9 \times 9 = 81 \][/tex]
[tex]\[ 4 \times 4 = 16 \][/tex]
Adding them together:
[tex]\[ 81 + 16 = 97 \][/tex]
This is equivalent to 97.
4. [tex]\((9 + 9) + (4 + 4)\)[/tex]
[tex]\[ 9 + 9 = 18 \][/tex]
[tex]\[ 4 + 4 = 8 \][/tex]
Adding them together:
[tex]\[ 18 + 8 = 26 \][/tex]
This is not equivalent to 97.
After careful evaluation, the expression that is equivalent to [tex]\(9^2 + 4^2\)[/tex] is [tex]\((9 \times 9) + (4 \times 4)\)[/tex].
Thus, the correct answer is:
[tex]\[ (9 \times 9) + (4 \times 4) \][/tex]
Let's start by evaluating [tex]\(9^2 + 4^2\)[/tex].
[tex]\[ 9^2 \][/tex] means 9 multiplied by itself, which is:
[tex]\[ 9 \times 9 = 81 \][/tex]
[tex]\[ 4^2 \][/tex] means 4 multiplied by itself, which is:
[tex]\[ 4 \times 4 = 16 \][/tex]
Adding them together:
[tex]\[ 81 + 16 = 97 \][/tex]
Now we will check each provided option to find which one equals 97.
1. [tex]\((9 + 4)^2\)[/tex]
[tex]\[ 9 + 4 = 13 \][/tex]
[tex]\[ 13^2 = 13 \times 13 = 169 \][/tex]
This is not equivalent to 97.
2. [tex]\((9 \times 4)^2\)[/tex]
[tex]\[ 9 \times 4 = 36 \][/tex]
[tex]\[ 36^2 = 36 \times 36 = 1296 \][/tex]
This is not equivalent to 97.
3. [tex]\((9 \times 9) + (4 \times 4)\)[/tex]
[tex]\[ 9 \times 9 = 81 \][/tex]
[tex]\[ 4 \times 4 = 16 \][/tex]
Adding them together:
[tex]\[ 81 + 16 = 97 \][/tex]
This is equivalent to 97.
4. [tex]\((9 + 9) + (4 + 4)\)[/tex]
[tex]\[ 9 + 9 = 18 \][/tex]
[tex]\[ 4 + 4 = 8 \][/tex]
Adding them together:
[tex]\[ 18 + 8 = 26 \][/tex]
This is not equivalent to 97.
After careful evaluation, the expression that is equivalent to [tex]\(9^2 + 4^2\)[/tex] is [tex]\((9 \times 9) + (4 \times 4)\)[/tex].
Thus, the correct answer is:
[tex]\[ (9 \times 9) + (4 \times 4) \][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.